2002
DOI: 10.1081/clt-120016962
|View full text |Cite
|
Sign up to set email alerts
|

Serum Acetylcholinesterase and Prognosis of Acute Organophosphate Poisoning

Abstract: In the acute phase of organophosphate poisoning, low serum acetylcholinesterase (> 50% of minimum normal value) supports the diagnosis of organophosphate poisoning but it does not show a significant relationship to the severity of poisoning (NS). The serum acetylcholinesterase activity may be a useful parameter in following the acute prognosis of organophosphate poisoning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
105
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(114 citation statements)
references
References 22 publications
5
105
0
4
Order By: Relevance
“…Goswamy et al have stated that measurement of the acetylcholinesterase level is useful in predicting the prognosis in OP poisoning,13 but the dominant view is that there is no relationship. In a study conducted by Aygun et al on patients with OP poisoning, acetylcholinesterase levels on admission were evaluated, and low levels of serum acetylcholinesterase were reported to support the diagnosis of acute OP poisoning, but acetylcholinesterase levels were not related to clinical severity 14. In the study conducted by Cherian et al on 21 patients with OP poisoning, no significant difference was found in serum acetylcholinesterase levels between the group treated with pralidoxime and the group that received placebo 15.…”
Section: Discussionmentioning
confidence: 99%
“…Goswamy et al have stated that measurement of the acetylcholinesterase level is useful in predicting the prognosis in OP poisoning,13 but the dominant view is that there is no relationship. In a study conducted by Aygun et al on patients with OP poisoning, acetylcholinesterase levels on admission were evaluated, and low levels of serum acetylcholinesterase were reported to support the diagnosis of acute OP poisoning, but acetylcholinesterase levels were not related to clinical severity 14. In the study conducted by Cherian et al on 21 patients with OP poisoning, no significant difference was found in serum acetylcholinesterase levels between the group treated with pralidoxime and the group that received placebo 15.…”
Section: Discussionmentioning
confidence: 99%
“…8 As of today only very few studies has shown that serum cholinesterase (ChE) and CPK level estimations are useful in diagnosis of organophosphorus poisoning in acute phase. 9,10 Hence, this study was planned for assessing CPK as a diagnostic and prognostic marker in patients with acute organophosphorus compound poisoning.…”
mentioning
confidence: 99%
“…[19,20] Aygun ve ark. 'nın [21] hastaneye OF zehirlenmesi ile başvu-ran hastalar ile yaptıkları bir çalışmada, hastaların başvuru-dan itibaren seri KE düzeyleri değerlendirilmiş ve düşük serum KE seviyesinin akut organik fosfor zehirlenmesinin tanı-sını desteklediği, fakat klinik şiddeti ile ilişkili olmadığı bildirilmiştir.…”
Section: Discussionunclassified